IFNγ, TNFα polymorphisms and IFNγ serum levels are associated with the clearance of drug-resistant P. falciparum in Malian children. (April 2023) - Kouriba, Bourema; Arama, Charles; Ouologuem, Dinkorma T.; Cissoko, Yacouba; Diakite, Mahamadou; Beavogui, Abdoul Habib; Wele, Mamadou; Tekete, Mamadou; Fofana, Bakary; Dama, Souleymane; Maiga, Hamma; Kone, Aminatou; et al.
Abstract: Host immunity has been suggested to clear drug-resistant parasites in malaria-endemic settings. However, the immunogenetic mechanisms involved in parasite clearance are poorly understood. Characterizing the host's immunity and genes involved in controlling the parasitic infection can inform the development of blood-stage malaria vaccines. This study investigates host regulatory cytokines and immunogenomic factors associated with the clearance of Plasmodium falciparum carrying a chloroquine resistance genotype. Biological samples from participants of previous drug efficacy trials conducted in two Malian localities were retrieved. The P. falciparum chloroquine resistance transporter ( Pf crt) gene was genotyped using parasite DNA. Children carrying parasites with the mutant allele ( Pf crt-76T) were classified based on their ability to clear their parasites. The levels of the different cytokines were measured in serum. The polymorphisms of specific human genes involved in malaria susceptibility were genotyped using human DNA. The prevalence of the Pf crt-76T was significantly higher in Kolle than in Bandiagara (81.6 % vs 38.6 %, p  <  10 −6 ). The prevalence of children who cleared their mutant parasites was significantly higher in Bandiagara than in Kolle (82.2 % vs 67.4 %, p < 0.05 ). The genotyping of host genes revealed that IFN-γ –874 T and TNF-α –308A alleles were positively associated with parasite clearance. Cytokine profiling revealed that IFN-γ level was positively associated with parasite clearance ( p = 0.04 ). This study highlights the role of host's immunity and immunogenetic factors to clear resistant parasites, suggesting further characterization of these polymorphisms may help to develop novel approaches to antiparasitic treatment strategies.